The Effect Of Executive Compensation And Board Of Director’s Gender Diversity To Tax Aggressiveness - Indrawan Wijaya (Penerbit Jurnal Indonesia, 2021)
This study aims to examine the influence of executive compensation and board of director’s gender diversity on tax aggressiveness the companies. This study utilizes quantitative method and multiple linear regression as statistical testing. This study is uses secondary data from companies financial reports and annual reports. Population in this study is manufacturing companies listed on Indonesia Stock Exchange in 2015-2019. Research samples were selected using purposive sampling method with 447 companies were considered to fulfilling the criteria. This study utilizes SPSS version 26 program as the processing data tool. The result of this study shows that executive compensation significantly and negatively influences the tax aggressiveness, while gender diversity doesn’t have any significant influence on tax aggressiveness.